The effects of Instagram media usage frequency of females in an urban public high school on perceptions of body-image for teenage female athletes and non-athletes. - Bohn, A. (The Young Researcher)
The purpose of this study was to examine the effects of photo-based media frequency on teenage females who attend an urban public high school and identify differences between athletes and non-athletes within that group. In order to determine the relationship of body image with media frequency, twenty participants were tested during a mixed correlational study where individuals completed a Likert-scale and open-response questionnaire. Responses included quantitative sums of Likert-scaled questions and qualitative quotes from open responses. Quantitative scores were correlated to media frequency through Linear Regression, while qualitative scores were coded and quantified to be compared to athletic participation. It was found that results were not statistically significant; however, a general negative correlation between media frequency and body image was calculated, meaning as frequency increases, teenage female body image decreases. Furthermore, quantified quotes revealed a positive correlation with athletic participation, so as a sport interaction increases, so does female adolescent body image.